2000
DOI: 10.1353/nas.2004.0001
|View full text |Cite
|
Sign up to set email alerts
|

Use of Jessor's Theoretical Framework of Adolescent Risk Behavior in Ethiopia: Implications for HIV/AIDS Prevention

Abstract: Objectives: To identify determinants of sexual behaviors among Ethiopian secondary school adolescents using Jessor's theoretical framework. Methods: A cross-sectional study design was used to examine determinants of sexual behaviors among 537 high school students aged 14-20. HIV risk and protective factors were identified based on a review of the literature. Focus group discussions and informal interviews were carried out to validate theoretical constructs and, together with the literature review, to guide que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
9
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 20 publications
3
9
0
Order By: Relevance
“…This finding is similar to studies conducted in many countries (8, 34, 35, 36). Numerous studies recommended family interventions to improve parent-child communication, supportive parenting, and parental monitoring.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This finding is similar to studies conducted in many countries (8, 34, 35, 36). Numerous studies recommended family interventions to improve parent-child communication, supportive parenting, and parental monitoring.…”
Section: Discussionsupporting
confidence: 92%
“…connectedness between parents and adolescents is linked to avoidance or lower use of alcohol, tobacco, and drugs and is less likely to initiate sex or sexual activity. On the contrary, poor-quality parent-youth relationships were associated with increased sexual activity (34, 35, 36). …”
Section: Discussionmentioning
confidence: 99%
“…Many studies also indicated that secondary school students are becoming sexually active at an increasing earlier age [9][10][11]. This early initiation of sexual activity prolongs the period of exposure to risk of pregnancy and risk of contacting STDs, including HIV infection during the reproductive span.…”
Section: Discussionmentioning
confidence: 99%
“…Family connected-ness is protective factor for risk sexual behavior. Several studies have found that positive relationship or connected-ness between parents and adolescents is linked to avoidance or lower use of alcohol, tobacco, and drugs and less likely to initiate sex [26][27][28] . Family supports were significantly associated with risky sexual behavior as protective factors.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is also consistent with many other findings. Meta-analysis of "youth-focused" prevention strategies aimed at delaying sexual intercourse and reducing risky sexual behavior found no evidence of beneficial effects In contrast, numerous family interventions focused on improving parent-child communication, supportive parenting, and parental monitoring have shown effects on these outcomes [26][27][28] .…”
Section: Discussionmentioning
confidence: 99%